HEVC perceptual intra-frame rate control inspired by video subjective observation experiment - Yanchao GONG; Ling WANG; Ying LIU; Kaifang YANG; Qingfan LIN; Fuping WANG (Tongxin xuebao)
In view of the low perceptual rate-distortion performance of the rate control method used in high efficiency video coding (HEVC), an intra-frame rate control algorithm to effectively improve the perceptual rate-distortion performance of video was proposed.First, the spatiotemporal complexity of videos was measured, and the video subjective observation experiment was designed combined with the spatiotemporal complexity.Secondly, based on the experimental results of video subjective observation, combined with the relevant human vision system perception characteristics, the spatiotemporal perceptual sensitivity factors of video content which could effectively measure the perception difference of human eyes for different regions of video were constructed.Finally, the spatiotemporal perceptual sensitivity factors were applied to the target bit allocation of the largest coding unit layer in the intra-frame image, then the perceptual intra-frame rate control was realized.Experimental results show that the proposed algorithm is superior to the rate control algorithm adopted by HEVC in terms of the bit estimation accuracy and the perceptual rate-distortion performance.